Farmers Response to the Partnership System in Broiler Chicken Livestock Business in East Lombok District - Muhamad Yasin (Postgraduate, University of Mataram, 2024)
This study aims to describe the response of farmers, and to analyze the correlation between selected characteristics of farmers and farmers' responses to the partnership system in broiler chicken farming businesses in East Lombok Regency, West Nusa Tenggara Province. The study was conducted from April to July 2021 using a descriptive-correlational method. In this study, 30 plasma farmers were selected as respondent samples using proportional random sampling. Measurement of variables, both independent variables and dependent variables, was carried out using an ordinal scale and a scoring system. Data analysis was carried out descriptively and using the Spearman Rank correlation statistical test. The results of the study showed that farmers' responses to the partnership system in broiler chicken farming businesses generally included good or positive criteria, and the correlation between several selected characteristics and farmers' responses varied from weak to strong. Two characteristic variables that were strongly correlated with farmers' responses to the partnership system in broiler chicken farming businesses were education level (p <0.01) and partnership motivation (p, 0.05).